The influence of work motivation, loyalty, and employee quality on employee performance at PT Ho Wah Genting Batam - Debora Winda Sari Simanjuntak; Alice Erni Husein (Trigin Publisher, 2026)
This study examined the influence of work motivation, loyalty, and employee quality on employee performance at PT Ho Wah Genting Batam. The research applied a quantitative descriptive and causal approach using primary data collected through questionnaires distributed to 152 employees selected from a population of 250 production department employees based on the Krejcie and Morgan sampling table. Data were analyzed using SPSS 26 through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test. The findings demonstrated that work motivation, loyalty, and employee quality positively and significantly affected employee performance both partially and simultaneously. The t-test results showed that work motivation had a significant effect on employee performance with a significance value of 0.029, loyalty with 0.005, and employee quality with 0.022, all below the 0.05 threshold. Simultaneously, the variables significantly influenced employee performance, as reflected by an F-count of 103.603 and a significance value of 0.000. The coefficient of determination indicated that 34.6% of employee performance variation could be explained by work motivation, loyalty, and employee quality, while the remaining percentage was influenced by other variables outside the research model. These findings confirm that improving employee motivation, strengthening organizational loyalty, and enhancing employee quality are essential strategies for optimizing employee performance within manufacturing companies.